The relationship between periodontal disease and low birth weight, preterm delivery and preeclampsia: A narrative review of descriptive studies - Amir Hossein Fathi; Seyed Sasan Aryanezhad; Ehsan Mostajeran; Ulduz Zamani Ahari; Seyedeh Mohadeseh Asadinejad (Mashhad University of Medical Sciences, 2022)
Introduction: Very limited studies have been performed on the relationship between periodontal disease and its effect on pregnancy outcomes; therefore, this study was performed aimed to investigate the relationship between periodontal disease and low birth weight, preterm delivery, preterm delivery with low birth weight and preeclampsia. Methods: This review study was performed by searching for the articles published in the period 2000 to 2020 with searching for the keywords of pregnancy, outcome, adverse, low weight, birth, abortion, preterm delivery, preeclampsia and periodontal in Pubmed, Scopus, Science Direct and Cochrane and Google Scholar and Embase in English language (lack of Persian article). Results: A total of 47 articles entered the final stage and found the relationship between periodontal disease and low birth weight, preterm delivery, preterm delivery with low birth weight and preeclampsia that can increase the risk of these complications. Conclusion: Periodontal diseases can increase the risk of low birth weight, preterm delivery, preterm delivery with low birth weight and preeclampsia